A method for determining supernatant-free spectra generated from fluorescently stained cells in suspension - Plášek, Jaromír; Gášková, Dana (Journal of photochemistry and photobiology. B, Biology, 2014)
Here we present a fluorometric method for direct determination of supernatant-free fluorescence spectra generated from fluorescently stained cells in suspension. The key element in the new technique is the design of an adapter to a standard cuvette holder that makes it possible to measure front-face fluorescence spectra from thin layers of cells spun down to the bottom of a spectrofluorometric cuvette. We have demonstrated the applicability of this approach and its analytical potential using the suspensions of yeast cells stained with the potentiometric dye of 3,3'-dipropylthiadicarbocyanine, diS-C3(3), and with the specific cell-wall marker calcofluor.
Keywords: Saccharomyces cerevisiae; Spectrometry, Fluorescence; membránové potenciály; karbocyaniny; fluorescenční spektrometrie; Carbocyanines; Membrane Potentials